Self-Efficacy in Mathematics: A predictor in the Mathematics performance of grade 8 learners - Campanilla, Noveen S. (Goodwood Publishing, 2025)
Purpose: This study was conducted to determine the respondents’ mathematics self-efficacy and their mathematics performance. It also pursues predicting the academic performance in mathematics of Grade 8 learners through their mathematics self-efficacy. Research methodology: The study was conducted on 159 Grade 8 students at Matucay National High School and examined the relationship between the learners' mathematics performance and their self-efficacy towards mathematics and looked for its impact on their academic performance using regression analysis. Results: The study reveals that students have average performance in mathematics and moderate confidence in their mathematics self-efficacy. The study also found that students' mathematics self-efficacy predicts their academic performance in mathematics. Thus, it is suggested that the students’ mathematics self-efficacy should be boosted to have a higher academic achievement. Limitations: The study investigates the link between students' mathematics self-efficacy and academic performance, emphasizing the need for effective teaching strategies to enhance students' perception of mathematics as a fun and interesting subject. Contribution: The study analyzed grade 8 students, examining if academic self-efficacy predicts academic performance. Results of the study may vary based on grade level and subject learning area.